Modified Shock Index as Simple Clinical Independent Predictor of In-Hospital Mortality in Acute Coronary Syndrome Patients: A Retrospective Cohort Study - Pramudyo, Miftah; Marindani, Vani; Achmad, Chaerul; Putra, Iwan Cahyo Santosa (Frontiers in Cardiovascular Medicine, 2022)
Introduction Despite being the current most accurate risk scoring system for predicting in-hospital mortality for patients with acute coronary syndrome (ACS), the Global Registry of Acute Coronary Events (GRACE) risk score is time consuming due to the requirement for electrocardiography and laboratory examinations. This study is aimed to evaluate the association between modified shock index (MSI), as a simple and convenient index, with in-hospital mortality and revascularization in hospitalized patients with ACS. Methods A single-centered, retrospective cohort study, involving 1,393 patients with ACS aged ≥ 18 years old, was conducted between January 2018 and January 2022. Study subjects were allocated into two cohorts: high MSI ≥ 1 (n = 423) and low MSI < 1 group (n = 970). The outcome was in-hospital mortality and revascularization. The association between MSI score and interest outcomes was evaluated using binary logistic regression analysis. The area under the curve (AUC) between MSI and GRACE score was compared using De Long’s method. Results Modified shock index ≥ 1 had 61.1% sensitivity and 73.7% specificity. A high MSI score was significantly and independently associated with in-hospital mortality in patients with ACS [odds ratio (OR) = 2.72(1.6–4.58), p < 0.001]. However, ST-segment elevation myocardial infarction (STEMI) and non-STEMI (NSTEMI) patients with high MSI did not significantly increase the probability of revascularization procedures. Receiver operating characteristic (ROC) analysis demonstrated that although MSI and GRACE scores were both good predictors of in-hospital mortality with the AUC values of 0.715 (0.666–0.764) and 0.815 (0.775–0.855), respectively, MSI was still inferior as compared to GRACE scores in predicting mortality risk in patients with ACS (p < 0.001). Conclusion Modified shock index, particularly with a score ≥ 1, was a useful and simple parameter for predicting in-hospital mortality in patients presenting with ACS.